Elderly Male Patient with Fibrotic Non Spesific Instertitial Pneumonia from Lung Biopsy by Video Assisted Thoracoscopy - santony, Santony; Djajalaksana, Susanthy; Chozin, Iin Nur; Erawati, Dini Rachma; Yudhanto, Hendy Setyo (Malang Respiratory Journal, 2020)
Background: NSIP is a rare disease, the incidence rate ranges from 1 to 9 per 100,000 population, where most cases of NSIP are idiopathic. NSIP definitive diagnosis is very difficult because it must be with a multidisciplinary approach and confirm from a pulmonary biopsy. On the course of his illnesses the possibility of Connective tissue diseases (CTDs) arising in NSIP during follow up period was about 10% of cases.Case Report: We reported one case at RS Dr. Saiful Anwar, an old adult male smoker, age 64 with fibrotic type Non Spesific Instertitial Pneumonia (NSIP). From clinical patients including anamnesis, physical examination and laboratory results and X-Ray chest, ILD suspicion was found. Bodypletstimography results show a corresponding decrease in DLCO with ILD. CT-Scan results obtained by crazy paving with pulmonary bronchiectasis traction in accordance with ILD susp Sussection NSIP and enforced from VATS biopsy results with conclusions according to NSIP description. Patients received corticosteroid therapy for 4 weeks and showed clinical improvement.Conclusion: In these patients the diagnosis of fibrotic NSIP has gone through a multidisciplinary approach including the pulmonology, radiologist and pathologist sections. Corticosteroid therapy in these patients gives good results and the patient is in stable condition. Periodic monitoring is necessary because of the risk of exacerbations and the incidence of CTD complications..